Parenting and Maternal Knowledge Factors on the Incidence Of Stunting in Toddlers in Bonto Salama Village, West Sinjai - Sri Sukmawaty Syahrir (Jurnal Gizi dan Kesehatan Keluarga, 2024)
Short and very short toddlers (stunting) is a nutritional status problem in children based on the height-for-age index (TB/U), with a prevalence of 144 million children under five in the world suffering from stunting. and maternal knowledge and parenting are important things that can be associated with stunting in toddlers. Objective: This study aims to determine the factors of parenting patterns and maternal knowledge on the incidence of stunting in toddlers in the village of bonto Salama West Sinjai. Methods: The type of research used in this study is analytic with crossectional design. This research was conducted in September-October 2023 at the West Sinjai Bonto Salama Village Health Center with the population in this study were all stunting toddlers, namely 26 toddlers. Results: The results of the study with the chi-square test showed that there was a relationship between maternal knowledge (p=0.000 <0.05) and there was no relationship between maternal parenting (p=0.725>0.05) with the incidence of stunting in Bonto Salama Village, West Sinjai.Conclusion: There is a relationship between maternal knowledge, and there is no relationship between maternal parenting and the incidence of stunting at the Tangngalembang Community Health Center, Bonto Salama Village, West Sinjai.